Pastoral health care and some of medicine's social responsibilities - Antico, Leonardo (Medicina e Morale, 1990)
Since there is an increasingly widespread concept that the quality of life is limited to economic capacity, physical efficiency and the ability to enjoy life, medical science proposes a global vision of the person in the unity of mind and body. According lo the author, medicine has a social responsibility towards the recovery of the dynamic balance between the person's mind, body and soul. Universities can play an important part in this by preparing generai practitioners and specialists more specifically and by providing for the study of the causes of premature dealh and invalidity (drugs, cigarettes, accidents at work etc.), the aging of the population, chronical diseases and home care.